Impact of functional and technical quality on patient satisfaction in prosthetic and orthotic care: A cross-sectional study - Mahmoud Alfatafta; Nizar Alsubahi; Huda Alfatafta; Huthaifa Atallah; Amneh Alshawabka; Anthony McGarry; Alaeddin Ahmad (PLoS ONE, 2025)
Patient satisfaction with prosthetic and orthotic services is shaped by both functional quality, such as communication and service accessibility, and technical quality, including device durability and usability. This study examined how these dimensions are associated with patient satisfaction in diverse healthcare settings in Jordan, a low- to middle-income country. A cross-sectional survey of 307 users from government, military, private, and non-governmental (NGO) providers was conducted using a 28-item questionnaire developed from existing literature. Confirmatory factor analysis and structural equation modeling confirmed the scale’s validity and tested associations between variables. Both functional quality (β = 0.521, p < 0.001) and technical quality (β = 0.382, p < 0.001) were significantly associated with satisfaction, with functional quality showing a stronger influence. NGO users reported the highest satisfaction scores, and the model explained 41.7% of the variance in satisfaction. ANOVA results revealed statistically significant differences among provider types. These findings highlight the value of patient-centered care and suggest that enhancing communication, accessibility, and service responsiveness may improve satisfaction, particularly in public and private sectors.